Prevalence of the bifid mandibular condyle and its relationship with pathologies of the temporomandibular joint: a systematic review and meta-analysis - Valenzuela Fuenzalida, Juan José.; Navarro, Kora-lle; Urbina, Pia; Trujillo Riveros, Martin.; Nova Baeza, Pablo.; Orellana Donoso, Mathias Ignacio.; Rodríguez Luengo, Macarena.; Becerra Farfán, Álvaro.; Sanchis Gimeno, Juan A. (MDPI, 2023)
Objective: The aim of this study was to describe the prevalence of anatomical variants in the bifid mandibular condyle (BMC) and report its association with temporomandibular joint (TMJ) pathology. Methods: We searched the Medline, Scopus, Web of Science, Google Scholar, CINAHL, and LILACS databases from their inception up to September 2023. Two authors independently performed the search, study selection, and data extraction, and they also assessed the methodological quality with an assurance tool for anatomical studies (AQUA). Finally, the pooled prevalence was estimated using a random effects model. Results: A total of 50 studies met the eligibility criteria. Twenty studies, with a total of 88,625 subjects, were included in the meta-analysis. The overall prevalence of the bifid mandibular condyle (BMC) variant was 1% (95% CI = 1% to 2%). Conclusions: The correlation between the BMC and TMJ pathologies has a relatively low prevalence in studies that present a considerable number of subjects. From a clinical point of view, a direct association cannot be made between the presence of the BMC and TMJ pathologies or symptoms.
Keywords: Anatomy mandibular condyle; Bifid mandibular condyle; Trifid mandibular condyle; Anatomy - Variation; Clinical anatomy; Articulación temporomandibular - Patología